NFE2L1 as a central regulator of proteostasis in neurodegenerative diseases: interplay with autophagy, ferroptosis, and the proteasome - Khodadadi, Hossein; Łuczyńska, Kamila; Winiarczyk, Dawid; Leszczyński, Paweł; Taniguchi, Hiroaki (Frontiers in Molecular Neuroscience, 2025)
Maintaining proteostasis is critical for neuronal health, with its disruption underpinning the progression of neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s diseases. Nuclear Factor Erythroid 2-Related Factor 1 (NFE2L1) has emerged as a key regulator of proteostasis, integrating proteasome function, autophagy, and ferroptosis to counteract oxidative stress and protein misfolding. This review synthesizes current knowledge on the role of NFE2L1 in maintaining neuronal homeostasis, focusing on its mechanisms for mitigating proteotoxic stress and supporting cellular health, offering protection against neurodegeneration. Furthermore, we discuss the pathological implications of NFE2L1 dysfunction and explore its potential as a therapeutic target. By highlighting gaps in the current understanding and presenting future research directions, this review aims to elucidate NFE2L1’s role in advancing treatment strategies for neurodegenerative diseases.